Biombalance™, an Oligomeric Procyanidins-Enriched Grape Seed Extract, Prevents Inflammation and Microbiota Dysbiosis in a Mice Colitis Model - Mokrani, Mohamed; Saad, Naima; Nardy, Ludivine; Sifré, Elodie; Despres, Julie; Brochot, Amandine; Varon, Christine; Urdaci, Maria C. (Antioxidants, 2025)
Inflammatory bowel disease (IBD) results from genetic factors, environmental factors, and intestinal microbiota interactions. This study investigated the effects of Biombalance™ (BB) in dextran sulphate sodium (DSS)-induced colitis in mice. BB extract exhibits high antioxidant activity, as determined by DPPH and ORAC tests. Mice were fed a standard diet, and BB was administered by gavage for ten days, before administration of 2.75% DSS in drinking water. BB significantly protected mice against DSS effects, as assessed by colon length, disease activity index (DAI) scores and colonic pathological damage. In addition, BB inhibited the expression of proinflammatory markers, such as IL-6, IL-17, CXCL1 and TNF-α, and the inflammatory mediators iNOS, TGF-β, FoxP3 and F4/80, while increasing IL-10 expression in the colon. BB modified microbiota composition, attenuating the microbial diversity lost due to DSS, increasing beneficial bacteria like Muribaculum, Lactobacillus, Muscispirillum, Roseburia and Bifidobacterium, and decreasing potentially harmful bacteria such as Proteobacteria and Enterococcus. Interestingly, microbiota-predicted functions using PICRUSt revealed that BB extract increases the antioxidant superpathway of ubiquinol biosynthesis, including ubiquinol-7, 8, 9 and 10 (CoenzymesQ). These findings suggest that Biombalance™ administration may help to reduce gut inflammation and oxidation, at least partly through modifications of the microbiota and its metabolites.